Fermentation of Banana Stems with Indigofera sp using MA-11 on Dry Matter and Organic Matter Digestibility - Bayu Santoso; Engkus Ainul Yakin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The limited availability of quality feed, especially during the dry season, encourages the use of agricultural waste as an alternative livestock feed. Fermentation with the addition of microbes has been widely used to improve feed quality, but information regarding the optimal dosage of MA-11 in a mixture of banana stems (Musa paradisiaca) and Indigofera sp. is still limited. The most effective dosage of MA-11 for increasing dry matter and organic matter digestibility in the fermentation of a mixture of banana stems and Indigofera sp. The study aimed to determine the most effective dosage of MA-11 for increasing dry matter and organic matter digestibility in a mixture of banana stems (Musa paradisiaca) and Indigofera sp. The study used a Completely Randomized Design (CRD) with three MA-11 dosage treatments: P0 (0 mL), P1 (1 mL), and P2 (2 mL), each replicated four times. The fermentation process was carried out for 12 days and was followed by a two-stage in vitro digestibility test. Data were analyzed using ANOVA followed by Duncan's Test (DMRT) at a significance level of P < 0.05. MA-11 administration significantly increased dry matter and organic matter digestibility. The best treatment was achieved at a dose of 2 mL (P2). Improved feed quality is influenced by the activity of cellulolytic, proteolytic, and amylolytic bacteria in MA-11, which are capable of breaking down crude fiber into simpler compounds. Fermenting banana stem waste combined with *Indigofera* sp. using MA-11 can improve feed quality, particularly dry matter and organic matter digestibility.